A Qualitative Dynamic System Approach Post Covid-19 Recovering Strategy on the MSME and Tourism Sector of Cirebon, West Java - ‎ , Lathifaturahmah; Vidiati, Cory; Syafei, Rachmat; Yuniawati, Rosdita Indah; Susilo, Yuyud (KnE Social Sciences, 2024)
This paper examines the government’s strong interest in Indonesia’s economic activities, especially in the context of post-COVID-19 economic recovery. The objective is to qualitatively analyze economic recovery strategies, especially in the MSME and tourism sectors, which have a significant impact on economic growth. A dynamic systems approach with qualitative methods was applied for collecting data through interviews, observations, and the use of secondary data from authentic articles. The findings highlight the need for support in the MSME sector, including improving the quality of human resources, financial management, tax incentives, credit relief and restructuring, increased working capital financing, product support, and e-learning training. The tourism sector requires innovation and diversification in the areas of product development, destinations, and tourism infrastructure management. This study makes a novel contribution by presenting a qualitative system dynamics conceptual model for post-COVID-19 economic recovery strategies. Future research will focus on testing and validating the components of this model in the context of MSMEs and tourism and will help policymakers, management teams, and relevant stakeholders in their efforts to recover MSMEs and tourism sectors from the impacts of disasters. This will have a significant impact on everyone involved. Keywords: Post COVID-19, MSMEs, tourism